Multicultural Studies, T. 1 (1/2016) (Zakład Pedagogiki Społecznej Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2016)
Although multiculturalism is a phenomenon strongly accented in the postmodern scientific discourse, the multitude of the aspects and processes manifested within multidimensional areas of human life and cultural communities (diversified by cultural differences) require current, up-to-date, precise, and innovative interpretation of its discursive, theoretical and empirical meanings.Undertaking this challenge, the themes tackled within the framework of the journal “Multicultural Studies” set on one hand, the proposed discourse in empirical foundation, revealing wide range of cutting-edge research and empirical perspectives investigating multiculturalism, and on the other focusing on the specificity of cultural indicators, as the latter are subject to ongoing transformation in the context of institutionally and informally manifested multiculturalism, i.e. within the framework of cultural transmission, socialization, acculturation, education, resocialization, intercultural education, as well as upon contacts with cultural difference within professional activities, etc.
Keywords: wielokulturowość; edukacja międzykulturowa